Navigating the bacterial cellulose alternative substrates landscape: a bibliometric study and thematic analysis - Quijano, Luis; Fischer, Dagmar; Rodrigues, Raquel; Wei, Yuanyuan (Cellulose, 2024)
Bacterial cellulose (BC) is a versatile and sustainable biomaterial with applications across various industries, including fashion and medicine. This study presents a bibliometric and thematic analysis of the research landscape surrounding BC production with the use of alternative substrates. The bibliometric review analyzed 198 papers selected via Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA), identifying 62 distinct academic disciplines, 906 keywords categorized into 6 clusters, and 98 journals contributing to the field. Of the dataset, approximately 57.6% of the papers were published in Q1 journals, 18.7% in Q2, 12.1% in Q3, 4.0% in Q4, 3.0% were not Q-ranked, and 4.5% were conference papers. The top 12 journals were all Q1 and held 42.9% of the dataset. Citation records, author networks, and keyword trends were examined using Publish or Perish 8 for citation analysis and VOSViewer for Author Network Analysis and keyword clustering. Thematic analysis identified key applications of BC in health and medicine, industry and materials, food and nutrition, electronics and energy, cosmetics and personal care, and environmental and green technology. Advantages such as high mechanical strength, biocompatibility, and biodegradability were frequently highlighted, making BC a preferred material in sustainability-driven industries. However, high production costs and yield/time limitations remain barriers to commercial adoption. The findings underscore the need for innovative solutions and interdisciplinary collaboration to enhance BC's commercial viability and sustainability. Graphical abstract: (Figure presented.)
CRIS-Team Scopus Importer:2024-12-06
Keywords: Alternative substrates; Applications; Bacterial cellulose; Bibliometric review; Keyword analysis; Thematic analysis